Factors Associated with the Incidence of Atopic Dermatitis in School-Age Children in the Working Area of the Waai Health Center in 2022 - Syulce Luselya Tubalawony; Deisperianty Tuasela; Griennasty Siahaya (UIMA Press, 2022)
Background: Atopic dermatitis is a global health issue if it is seen from the increasing prevalence and high cost of treating atopic dermatitis. Atopic dermatitis is an inflammation of the skin in the form of chronic residive dermatitis, accompanied by itching, and affecting certain body parts, especially in the face in infants (infantile phase) and sural parts of the extremities (in the child phase). Several triggering factors for atopic dermatitis include intrinsic factors such as genetics, characteristics of atopic skin, immunological disorders, stress, and extrinsic factors such as the environment, irritants, allergens, food, microorganisms, and weather. Objectives: The purpose of this study was to determine the relationship between genetics, food allergies, and the environment with the incidence of atopic dermatitis in the working area of ​​the Waai Health Center. Methods: The research design used was descriptive-analytical with a cross-sectional study approach. The population is all Elementary School 163 Central Maluku, Elementary School 224 Central Maluku, and Elementary School 25 Central Maluku which are in the working area of ​​the Waai Health Center, there are 433 children. Sampling with accidental sampling technique. The sample in this study found 208 children. Results: The results obtained a significant relationship between genetics, food allergies, and environment with the incidence of atopic dermatitis with a value (p = 0.000). Conclusion: It is recommended for families to supervise and supervise children if there is a history of atopy in family members to reduce the risk factors for atopic dermatitis in children because this atopic dermatitis cannot be cured but its recurrence can be controlled.